Implementation of the OSS-RBA and Its Implications for Public Administration Education - Siti Nurlela; Pandji Santosa (Civiliza Publishing, Indonesia., 2025)
Clinic licensing is an essential instrument to ensure legality and service quality in healthcare delivery. The Government of Sumedang Regency has implemented clinic licensing through the Online Single Submission Risk-Based Approach (OSS-RBA) system; however, several challenges remain in its implementation. This study aims to analyze the implementation of OSS-RBA-based clinic licensing policy in Sumedang Regency and to identify its supporting and inhibiting factors. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed using George C. Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the policy implementation has generally complied with existing regulations but has not yet reached optimal performance. Strengthening policy communication, improving resource capacity, simplifying procedures, and enhancing inter-agency coordination are necessary to improve the effectiveness of clinic licensing services.